Temporary Intercropping With Forage or Industrial Crops Improves Yield and Weed Control in Cardoon (Cynara cardunculus var. altilis DC) - Giorgia Raimondi; Pietro Todde; Pier Paolo Roggero; Laura Mula; Vittoria Giannini (GCB Bioenergy)
ABSTRACT Cardoon (Cynara cardunculus var. altilis) is a promising perennial energy crop for Mediterranean areas. Implementing temporary intercropping with selected species during the long establishment phase of the cardoon can enhance ecosystem services by promoting crop diversification, suppressing weeds, and increasing biomass production. A three‐year field experiment conducted in Sardinia, Italy, compared three intercropping systems: (i) rocket (Eruca sativa), (ii) camelina (Camelina sativa), and (iii) hairy vetch (Vicia villosa) with a monocropped control. The study assessed the effects of temporary intercropping on weed suppression and cardoon development and production. The biomass production of the intercropped species was also measured. Temporary intercropping reduced weed biomass by 24.2% on average (compared to the control) without hindering cardoon establishment in the first year of cultivation. V. villosa and E. sativa were the most competitive against the main weeds. V. villosa had the highest yield. Temporary intercropping with V. villosa, in the following year after its establishment, increased cardoon production by an average of 55.1% compared to the other intercropped species.